The Korean Financial Crisis of 1997-A Strategy of Financial Sector Reform - Ubide, Angel; Balino, Tomas (Washington, D.C. : International Monetary Fund, 1999)
After years of strong performance, Korea's economy entered a crisis in 1997, owing largely to structural problems in its financial and corporate sectors. These problems emerged in the second half of that year, when the capital inflows that had helped finance Korea's growth were reversed, as foreign investors-reeling from losses in other Southeast Asian economies-decided to reduce their exposure to Korea. This paper focuses on the sources of the crisis that originated in the financial sector, the measures taken to deal with it, and the evolution of key banking and financial variables in its aftermath.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet